Some aspects of the reproduction in the elongate sunset clam, Gari (Gabraeus) elongata (Lamarck 1818) from Banate Bay Area, West Central Philippines - Nabuab, Fenelyn; del Norte-Campos, Annabelle; del Norte-Campos, Annabelle (Science Diliman: A Journal of Pure and Applied Sciences; Vol 18 No 2 (2006), 2007)
Date submitted: January 27, 2006; Date accepted: October 13, 2006 The elongate sunset clam, Gari (Gabraeus) elongata (Lamarck 1818) is one of the commercially important invertebrates in Panay Island. The reproductive biology of this species from the Banate Bay Area, Panay Island, West Central Philippines was studied over one annual cycle. Elongate sunset clams were gathered monthly every last quarter of the lunar phase from September 2004 to August 2005.The shell length at first maturation, the sex ratio and the spawning periodicity were determined. The different stages of the reproductive cycle were characterized by histological examination. Seven distinguishable gonad stages were determined in both male and female clams namely, immature, early and late developing, mature, partially spawned, redeveloping and spent. Indeterminate gonads were also noted. Gari elongata is a dioecious species but in a few specimens hermaphroditism was observed. It exhibits no sexual dimorphism. The male to female ratio is 1:1.04. Sexual maturity is attained at 45.40 mm SL in the male and 44.80 mm SL in the female. It is therefore recommended that clams smaller than these sizes should not be collected to allow recruitment and proper sustainability of the resource. Based on the GSI and Index of Sexual Maturity elongate sunset clams have a protracted or continuous breeding period. Sexual activity is highest during the wet season while gamete development occurred during the preceding dry season. The latter is supported by higher phytoplankton densities.